Neonatales Abstinenzsyndrom bei europäischen und nordamerikanischen Neugeborenen: Unterschiede im klinischen Verlauf an Hand von Daten einer prospektiven randomisierten Studie - Kirchner, L.; Graf-Rohrmeister, K.; Klebermass-Schrehof, K.; Weninger, M.; Jagsch, R.; Metz, V.; Unger, A.; Fischer, G. (Klinische Pädiatrie, 2014)
Background: Due to the steady increase of substance-dependent pregnant women the neonatal abstinence syndrome has become an increasingly important issue in neonatology. The present study investigates site-specific differences of detailed symptoms and treatment of neonatal abstinence syndrome within the context of an international multicenter clinical trial.Methods: Site specific neonatal data analyses from a prospective randomized, double-blind, double-dummy clinical trial (MOTHER study) was performed. A standardized NAS rating and treatment protocol was applied, while non-pharmacological care of NAS symptoms differed across the sites.Results: Urban US neonates exhibited most neurological symptoms (p<0.001) while in Europe autonomous, respiratory and gastrointestinal symptoms were found significantly more often compared to urban and/or rural US (p<0.05). Methadone produced significantly greater scores than buprenorphine in neurological, behavioural and respiratory symptoms regardless of the sites (ps<0.05). NAS treatment rates in all site clusters were similar for methadone-exposed neonates, while in Europe significantly more buprenorphine-exposed neonates were treated (p=0.001) than in US site clusters. Urban US neonates had significantly higher NAS scores (p<0.01) compared to rural US and European neonates, and needed significantly higher morphine doses (p<0.05) with longer treatment duration. Birth weight, length and head circumference did not differ significantly among the site clusters, but APGAR scores were significantly higher in European (p<0.01) neonates.Conclusion: In addition to intrauterine medication exposure other aspects such as different addiction severity of the mothers, different treatment modalities including rooming-in as well as the frequency of NAS ratings may be influencing the course of NAS.
Keywords: intrauterine opioid exposure; neonatal abstinence syndrome; methadone; buprenorphine; morphine